PERSEPSI GURU TERHADAP PENERAPAN KURIKULUM MERDEKA DI SD NEGERI 2 TONJA DENPASAR - Wirayani, Ni Made; Mariani, Ni Nyoman; Tri Wahyuni, Ni Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aims to determine teachers' perceptions of the implementation of the independent curriculum which includes independent curriculum planning, implementation of the independent curriculum, and assessment of the independent curriculum that has been implemented at SD Negeri 2 Tonja Denpasar.The problems discussed in this research are 1) What are the teachers' perceptions of the independent curriculum planning?, 2) What are the teachers' perceptions of the implementation of the independent curriculum?, 3) What are the teachers' perceptions of the independent curriculum assessment?The type of research used in this research is descriptive research with a quantitative approach. The data collection technique used in this research is a questionnaire. The instrument used is a closed questionnaire. The place where this research was carried out was at SD Negeri 2 Tonja Denpasar for six months. The research population used was all homeroom teachers at SD Negeri 2 Tonja Denpasar. The research sample was all class teachers using a saturated sampling technique.The results of the research show that teachers' perceptions of planning in the independent curriculum are of good quality, teachers' perceptions of the implementation of the independent curriculum are of good quality, and teachers' perceptions of assessments in the independent curriculum are of good quality